The Role and Impact of Dyslexia Awareness Workshops in the Medical Curriculum - Mitchell Osei-Junior; Mayya Vorona (International Journal of Medical Students, 2023)
Background: To increase recognition of the number of students who study medicine with dyslexia and the support available, it is important to cultivate a culture in which peers can support fellow peers with dyslexia academically and pastorally. This study aims to understand medical students’ perceptions of dyslexia and confidence with supporting fellow peers with dyslexia before and after a workshop on dyslexia.